"Identificação e quantificação da flora microbiana de solos onde foram adicionados resíduos de açougue e serraria, Tailândia-Pa" - Ribeiro, Eliane Cristina Soares (Museu Paraense Emílio Goeldi, 2023)
In the Amazon there is an occurrence of soils that were formed from prehistoric human occupation. These soils are highly fertile and stable, called Terra Preta Arqueológica (TPA) (Kern 1988; Kern & Kãrmpf 1989; Kern 1996; Costa & Kern 1999). In order to reproduce the TPA, an experiment was set up in the municipality of Tailândia-PA, where residues from sawmills and butcher shops were used. Sixty-eight plots were dimensioned and installed, measuring 3x3 meters each, where the organic residues were added and mixed with the original local soil. The added wastes were: saw dust residue (RPS); ground blade residue (RLT); charcoal (C); bone, blood and fat residue (RA), in varying combinations. In addition to a control plot. This study aimed to quantify and identify the microbial population in the installed plots. Samples were collected in the dry and rainy periods of the years (2003 and 2004) at a depth of 0-5 cm. Laboratory analyses were performed for total bacterial and fungal counts, using the "pour plate" seeding method, with Standard Agar medium for bacteria and acidified Potato Agar for fungi. The identification phase performed by morphological and physiological tests is in progress. The results obtained up to the current stage of the study show that the average number of viable propagules per gram of dry soil was in the range of 10-5 CFU/g soil for bacteria and 10- 3 CFU/g soil for fungi. There was a general trend for the microbial community to be higher in the plots with higher residue diversity, except those with RA, compared to the original soil plot (B), although there was a significant difference among all the plots studied. The low number of microorganisms in the plots with butcher waste (bones, blood and fat) may be due to the monthly addition of blood in natura in the plots, which would be acidifying the soil.